STRATEGI MENGOPTIMALKAN PERAN DPS DALAM PENEGAKAN PRINSIP SYARIAH DI LEMBAGA KEUANGAN SYARIAH : Upaya Menjaga Sharia Compliance - Muhammad Syarif Hidayatullah (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
Islamic Financial Institutions are financial institutions whose operations are based on sharia principles. The business that is run must not have prohibited elements in its financial transactions such as riba, maysir and gharar. The presence of a Sharia economic fatwa issued by DSN-MUI becomes a guideline for LKS in formulating its financial products to be in accordance with sharia contracts. To maintain the implementation of sharia principles in LKS, there is a Sharia Supervisory Board as a representation of DSN-MUI whose position acts as a sharia compliance supervisor who is in charge of maintaining conformity between the DSN-MUI fatwa and the practice of financial products in LKS. The study in this paper aims to analyze the existence of DPS in LKS and then try to formulate strategies to optimize the role of DPS in controlling shariah compliance. The existence of DPS in LKS has a very important position in controlling shariah compliance and strategies that can be carried out in optimizing its role such as socializing about the role of DPS actively so that there is no more confusion about how the role of DPS, the selection of DPS which must prioritize capabilities (mastering contemporary Islamic economics and finance and fiqh muamalah) rather than just figuration, Furthermore, strengthening the position of DPS in order to have independence so that it is safe from potential intervention in the implementation of its duties.